Bordering on the modern: power, practice and exclusion in Astana. Issue 3 (17th September 2013) - Koch, Natalie
<x xml:space="preserve">Abstract</x> State‐led urban development projects, especially in non‐democratic settings, are conducive to a top–down analytic that focuses on state planners and architects. The goal of this article is to explore how we might decentre this narrative and jointly consider elite and non‐elite narratives, through an analysis of discourses of modernity as enacted in and through these statist urban projects. Deploying a practice‐based analytic, I explore how notions of 'modernity' are performed and enacted through the exclusionary practices of elites and non‐elites alike. Taking the case of Kazakhstan's new capital city, Astana, I examine how the state‐led urban modernisation agenda simultaneously draws upon and re‐inscribes a set of interlocking popular geographic imaginaries (Soviet/modern, urban/rural, north/south), and demonstrate how ordinary citizens are not just passive spectators, but active participants in the political drama of state‐ and city‐building.